Thermodynamics and P-v criticality of Bardeen-AdS black hole in 4D Einstein-Gauss-Bonnet gravity - Dharm Veer Singh (Physics Letters B, 2020)
We consider the Gauss-Bonnet corrected Bardeen black hole solution in 4D AdS space-time. The solution is obtained by the limiting procedure adopted by Glavan and Lin in 4D Einstein-Gauss-Bonnet gravity. The general form of first law of black hole thermodynamics is utilized to calculate various thermodynamics variables. The solution exhibits P-v criticality and belongs to the universality class of van-der Waals fluid. The effect of Gauss-Bonnet coupling is investigated on critical parameters and inversion temperature.